Prestasi Belajar Mahasiswa Penerima Bidik Misi Selama Masa Pandemi Covid-19 - Silaban, Nurmintan; Citra, Fevi Wira; Yunita, Mirna (JOEAI (Journal of Education and Instruction), 2021)
This study aims to see the achievements of Bidik Misi Scholarships of students during the Covid-19 outbreak at Prof. Dr. Hazairin University. This research was conducted using descriptive research methods. The population and samples used in this study are all students who received Bidik Misi Scholarships in the academic year Odd 2019/2020 and Even 2019/2020 who were studying as many as 219 students. Data collection technique is a documentary technique, a tool used in the form of a stuffing format designed in such a way that it can record all the necessary data. This research data is quantitative data that is analyzed using descriptive analysis and categorized based on Academic Guidelines. The results of the study, the achievement of students who received Bidik Misi Scholarships in the academic year 2019/2020 judging from the average cumulative achievement index of students in the Odd semester is 3.31 and the average cumulative achievement index of students in the Even semester is 3.24. The average academic achievement score of students seen from 219 students who received mission objectives decreased by 0.07 during the Covid-19 pandemic. The decrease in the index of learning achievement of mission-aiming students has been seen in the Aquaculture program wherein the odd semester before the pandemic the average academic achievement was 3.8 and the average academic achievement during the Covid-19 pandemic was 2.7. In conclusion, the percentage of cumulative achievement index of the average recipient of Bidik Misi Scholarships during the Covid-19 outbreak at Prof. Dr. Hazairin University in the category is very satisfactory or above 2.75. Keywords: Bidik Misi Scholarships, Covid-19, Learning Achievements